Procedury awaryjne przewidziane w Konstytucji kwietniowej z 1935 roku w sytuacji nieuchwalenia budżetu państwa - Halasz, Artur (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The subject of this article is the analysis of emergency procedures in case of failure to adopt the state budget, as regulated in the Polish April Constitution of 1935. However, the aim of this study is to indicate that the legislator in the April Constitution secured the Polish state against the phenomenon of a budget vacuum — that is, the lack of adoption of the budget and, consequently, the lack of grounds for managing the state’s financial economy. This thesis is confirmed based on the dogmatic-legal and historical-legal methods. Firstly, the budgetary procedure is analyzed. Secondly, the procedure of prorogation of the budget act is analyzed. The study will also compare the solutions adopted in the April Constitution and the currently applicable Constitution of the Republic of Poland of 1997.
Keywords: budżet; procedura budżetowa; ustawa budżetowa; konstytucja; prorogacja